2014
DOI: 10.1002/prep.201300148
|View full text |Cite
|
Sign up to set email alerts
|

Role of Additives in the Combustion of Ammonium Dinitramide

Abstract: The thermal decomposition behavior and combustion characteristics of mixtures of ammonium dinitramide (ADN) with additives were studied. Micrometer‐sized particles of Al, Fe2O3, TiO2, NiO, Cu(OH)NO3, copper, CuO, and nanometer‐sized particles of aluminum (Alex) and CuO (nano‐CuO) were employed. The thermal decomposition was measured by TG‐DTA and DSC. The copper compounds and NiO lowered the onset temperature of ADN decomposition. The heat value of ADN with Alex was larger than that of pure ADN in closed condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…[47] N 2ðgÞ þ3H 2 Ammonia production using renewable intermittent energy is technically feasible with current technologies. [48,49] Moreover,v arious ammonia-derived nitrogen-based fuels have been previously suggested, such as:A Na nd AN-based compositions, [50][51][52][53][54][55][56] aqueous hydroxylammonium nitrate, [57,58] ammonium dinitramide, [59][60][61][62] and aqueous AN with ammonium hydroxide or urea. [14] While the methanol economy addresses both the energy and the broad chemical sectors, [63,64] …”
Section: The Nitrogen Economymentioning
confidence: 99%
“…[47] N 2ðgÞ þ3H 2 Ammonia production using renewable intermittent energy is technically feasible with current technologies. [48,49] Moreover,v arious ammonia-derived nitrogen-based fuels have been previously suggested, such as:A Na nd AN-based compositions, [50][51][52][53][54][55][56] aqueous hydroxylammonium nitrate, [57,58] ammonium dinitramide, [59][60][61][62] and aqueous AN with ammonium hydroxide or urea. [14] While the methanol economy addresses both the energy and the broad chemical sectors, [63,64] …”
Section: The Nitrogen Economymentioning
confidence: 99%
“…[39,41] Ammoniak eignet sich mit geringen Anpassungen als Brennstoff in Benzin-und Dieselmotoren [42][43][44] sowie in Gasturbinen [45,46] und Raketenantrieben. [47] N 2ðgÞ þ3H 2 schungen, [50][51][52][53][54][55][56] wässriges Hydroxylammoniumnitrat, [57,58] Ammoniumdinitramid [59][60][61][62] und wässriges AN gemischt mit Ammoniumhydroxid oder Harnstoff [14] vorgeschlagen. Wäh-rend die Methanolwirtschaft für die Bereiche Energieerzeugung und Chemie im breiteren Sinn interessant ist, [63,64] Das für die Herstellung der kohlenstoffbasierten Kraftstoffe bençtigte CO 2 kann aus der Atmosphäre oder aus anthropogenen Quellen gewonnen werden.…”
Section: Die Methanolwirtschaftunclassified
“…A mixture of ammonium dinitramide (ADN) and ammonium nitrate (AN) allowing at least equivalent performance to those obtained with AP was selected as a green alternative. The replacement of this component implies to redesign the global composition of the propellant and more particularly to find adapted burning rate modifiers (BRM) in order to tailor the combustion [2].…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily to AN, few studies on BRM dedicated to ADN-based propellant can be found in the literature. Fujisato et al [5] studied the effect of different additives: Al, Fe 2 O 3 , TiO 2, NiO, Cu(OH)NO 3, CuO , nano-CuO and nano-Al (Alex). Decomposition temperature is lowered with nickel oxide and copper oxide as well as with borocarbonitride materials.…”
Section: Introductionmentioning
confidence: 99%